A REVIEW OF ANALYTICAL TECHNIQUES FOR DETERMINATION OF ANTI-HIV DRUGS - MISHRA, RAJEEV KUMAR; CHAUBEY, NEELESH; PATEL, JAY RAM; MISHRA, SATISH; SINGH, ROHIT (International Journal of Applied Pharmaceutics, 2020)
Pharmaceutical analysis plays a very prominent role in quality assurance as well as quality control of bulk drugs and pharmaceutical formulations. Rapid increase in pharmaceutical industries and production of drug in various parts of the world has brought a rise in demand for new analytical techniques in the pharmaceutical industries. As a consequence, analytical method development has become the basic activity of analysis. From the times of yore, people were trying to find safe and sound ways to treat viral infections. In the current scenario, due to the emerging of new viruses, the development of drugs for their treatment is also gaining equal importance. Before launching to the market, these drugs should undergo a validation process. High-performance liquid chromatography (HPLC) coupled with ultraviolet (UV), Photodiode array detectors (PDA), Mass spectrophotometer (MS) detectors etc. is one of the fastest, safe and precise technologies used for determination and separation of pharmaceutical drugs, impurities and biological samples. HPLC is versatile and it takes less time for quantification of drugs as compared to old liquid chromatography techniques. Tenofovir disoproxil fumarate (TDF), Emtricitabine (FTC) and Efavirenz (EFV) is antiretroviral medicine used treat AIDS as well as chronic Hepatitis-B. It is used alone or with other HIV medications to help control HIV infection. The present review article assesses the published analytical methods and a variety of approach for investigation of TDF, FTC and EFV in bulk drug as well as pharmaceutical formulations including combinations. The present studies revealed that HPLC technique along with the spectroscopic have been most widely explored for the analysis. The investigatory review may provide the comprehensive details to the researchers who are working in the area of analytical research of TDF, FTC and EFV.